Perbedaan Pijat Bayi Dengan Baby Oil Dan Minyak Telon Terhadap Berat Badan Bayi Usia 0-6 Bulan Di Polindes Buluh Socah - Iin Setiawati; NAILUFAR FIRDAUS (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Infants are children aged 0 to 12 months where growth and development are very fast. Weight growth of infants aged 0-6 months has increased by 150-210 grams/week. In January-February 2021, 4 babies did not gain weight from 30 babies aged 0-6 months who visited the polindes in Buluh Village. research purposes analyzed the difference between baby massage with baby oil and telon oil on the weight gain baby aged 0-6 months. This research was Quasi experimental research with a non-randomized pretest-posttest approach group design. The independent variable was infant massage and the dependent variable was an increase in infant weight. The population is 30 with a sample of 26 was taken non-randomly, which was then divided into 2 groups, namely baby massage with telon oil and baby massage with baby oil. Data testing was carried out use statistical test Independent T-test. The study results showed that the average increase in baby weight after being massaged with telon oil was 284.61 grams and after being massaged with baby oil 65.38 grams with the results independent t-test test, p-value = 0.000. So that it showed there is different of baby massage with baby oil and telon oil on increasing the weight of full-term infants aged 0-6 months. Telon oil has potential to increase the speed of weight loss. Possible, because the content coconut oil causes an increase in the absorption saturated fat levels infants which acts as a source for infant growth.